A bacterial extracellular vesicle‐based intranasal vaccine against SARS‐CoV‐2 protects against disease and elicits neutralizing antibodies to wild‐type and Delta variants. Issue 3 (14th March 2022) - Jiang, Linglei; Driedonks, Tom A.P.; Jong, Wouter S.P.; Dhakal, Santosh; Bart van den Berg van Saparoea, H.; Sitaras, Ioannis; Zhou, Ruifeng; Caputo, Christopher; Littlefield, Kirsten; Lowman, Maggie; Chen, Mengfei; Lima, Gabriela; et al.
Abstract: Several vaccines have been introduced to combat the coronavirus infectious disease‐2019 (COVID‐19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Current SARS‐CoV‐2 vaccines include mRNA‐containing lipid nanoparticles or adenoviral vectors that encode the SARS‐CoV‐2 Spike (S) protein of SARS‐CoV‐2, inactivated virus, or protein subunits. Despite growing success in worldwide vaccination efforts, additional capabilities may be needed in the future to address issues such as stability and storage requirements, need for vaccine boosters, desirability of different routes of administration, and emergence of SARS‐CoV‐2 variants such as the Delta variant. Here, we present a novel, well‐characterized SARS‐CoV‐2 vaccine candidate based on extracellular vesicles (EVs) of Salmonella typhimurium that are decorated with the mammalian cell culture‐derived Spike receptor‐binding domain (RBD). RBD‐conjugated outer membrane vesicles (RBD‐OMVs) were used to immunize the golden Syrian hamster ( Mesocricetus auratus ) model of COVID‐19. Intranasal immunization resulted in high titres of blood anti‐RBD IgG as well as detectable mucosal responses. Neutralizing antibody activity against wild‐type and Delta variants was evident in all vaccinated subjects. Upon challenge with live virus, hamsters immunized with RBD‐OMV, but not animals immunized with unconjugated OMVs or a vehicle control, avoided body mass loss, had lower virus titres in bronchoalveolar lavage fluid, and experienced less severe lung pathology. Our results emphasize the value and versatility of OMV‐based vaccine approaches.